MODERN TRENDS IN UPDATING ACCOUNTING AND REPORTING, CONTROL AND ANALYTICAL CONCEPTS OF INFORMATION SUPPORT OF MANAGEMENT DECISIONS - A. Bodyako; A. Bondarenko (Вестник университета)
The modernization of accounting and analytical systems, concepts of the digital economy as a phenomenon of understanding the goals of management are considered. The controversial aspects of upgrading accounting and reporting, control and analytical concepts of information support of management decisions are discussed. The conclusions has been drawn that the decision is strategically important and essential task of the implementation and management of large companies raises the question about the existence of objective needs to create a unified methodology (theory and practice) for accounting, analysis and control, to expansion of interpretations of the terms «integrated accounting» and «controlling». Taking into account the opinions of scientists the algorithm of information and technological process of preparation and obtaining relevant information for solving administrative problems has been formed. The using of this algorithm will increase the level of information support management decisions.